2018
DOI: 10.1590/2317-1545v40n3198414
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the physical and physiological quality of soybean seeds during processing

Abstract: Seed processing or conditioning is important for improving soybean seed lot quality as it improves the physical characteristics by eliminating inert materials, weed and non-standard seeds and increases physiological quality. The objective of this study was to evaluate the effect of processing on physical and physiological qualities of soybean seed, before and after each equipment and transport system, during processing in a Seed Processing Plant. Samples of six cultivars were obtained during processing while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
7
0
2
Order By: Relevance
“…The storage of seeds in permeable packagings allows the internal humidity to change with the environment, causing increases or decreases in the water content until reaching hygroscopic equilibrium (Rocha et al, 2017;Moreano et al, 2018;Keneni et al, 2019). Smaniotto et al (2014) evaluated the storage of soybean seeds and observed a reduction in the water content, to 11%, due to the permeability of the packaging, which allowed greater intensities of water vapor exchange with the environment.…”
Section: Resultsmentioning
confidence: 99%
“…The storage of seeds in permeable packagings allows the internal humidity to change with the environment, causing increases or decreases in the water content until reaching hygroscopic equilibrium (Rocha et al, 2017;Moreano et al, 2018;Keneni et al, 2019). Smaniotto et al (2014) evaluated the storage of soybean seeds and observed a reduction in the water content, to 11%, due to the permeability of the packaging, which allowed greater intensities of water vapor exchange with the environment.…”
Section: Resultsmentioning
confidence: 99%
“…In an evaluation of different storage environments at 10˚C, 25˚C, and room temperature, different deterioration rates were verified, influenced by the variation of the water contents. The predominant reaction of seed degradation occurred when the water content of the seeds reached levels below the activation limit for enzymatic lipid peroxidation and sugar hydrolysis [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The seed lots showed high physical and physiological quality since the reception, and the seeds reached greater purity, germination and vigor throughout the process, since the values increased with each stage. One of the premises of the beneficiation is to remove impurities and damaged or non-standard seeds, raising the quality to the final product (Lopes et al, 2011;Kirchner et al, 2014;Moreano et al, 2018). In control charts, upper control limits (ULC) and lower control limits (LLC) are established to help judge the significance of the variation in product quality.…”
Section: Resultsmentioning
confidence: 99%